Online Food Ordering System for Long Distance Express Coaches - Md Noh, Nurfarah Fatina (IRC, 2019)
The rampant growth of revolution industry 4.0 has brought fast pace changing in technology nowadays. The advancement of wireless network and mobile devices has created a powerful impact towards human lives through this era. The demands of this kind of advancement has created a lot of chances for all business sectors to upgrade efficiency in their system. This paper presents an idea where this advancement also can be utilised in hospitality sector that contributes in transportation industry such as airline, train, bus and others which located in Malaysia. The application named online food ordering system where it designed an online food ordering system for restaurants that located in the rest area from Sri Iskandar to Mersing which the express coaches will stop for a break. The application can be visualised by customers via mobile device that implements wireless access to the servers. The application will update the orders in nucleus database and simultaneously sent it to the respective restaurant’s cashier and the cooker which this will improve a great efficiency for the business. A few researchers such as Tanpure at al (2013) also supported that an online ordering system would reduce time and human lapse that will give huge advantages to the business in terms of system proficiency, convenience and food order accuracy instead of using queuing system. This emergence of communication technology can be a pleasing solution for the customers to be more comfortable while having a long journey across Malaysia in express coaches.